KAWASAN MINAPOLITAN TERHADAP EFEKTIVITAS PRODUKSI PERIKANAN DI KABUPATEN GORONTALO UTARA PROVINSI GORONTALO - Sukarman Kamuli (Indonesian Journal of Dialectics, 2011)
North Gorontalo Regency has a marine fisheries & aquaculture potential economic value. In response it, the government makes Minapolitan regional development policy. It is intended to enlarge the production of fisheries and aquaculture. However, the goal has not reached the target yet, because the implementation of policies have not been optimal. The purpose of this research is to measure and analyze the influence of regional development policy implementation Minapolitan toward the fisheries and aquaculture production.  The method used in this research is explanatory survey by using the quantitative approach. The population is the policy implementer that consists of  221 persons. The technique of choosing sample uses estimation rule of thumb, so the total sample is 70 persons. Then statistical testing uses Structural Equation Modeling (SEM) model. The testing result shows that the implementation of regional development policy Minapolitan effects on the effectiveness of fishery production significantly, in which the dimension of  the program implementers are able to reflect the variable implementation of development policy while the weak dimension is community leaders. The finding indicates that the implementation of the policy requires a dialogical approach, which is an approach that integrates both the interest of government and the public one.